Food-Derived High Arginine Peptides Promote Spermatogenesis Recovery in Busulfan Treated Mice - Liu, Wenwen; Zhang, Lingfeng; Gao, Anning; Khawar, Muhammad Babar; Gao, Fengyi; Li, Wei (Frontiers in Cell and Developmental Biology, 2021)
Food-derived peptides with high arginine content have important applications in medicine and food industries, but their potential application in the treatment of oligoasthenospermia remains largely elusive. Here, we report that high-arginine peptides, such as Oyster peptides (Opp) and Perilla purple peptides (Ppp), were able to promote spermatogenesis recovery in busulfan-treated mice. We found that both Opp and Ppp could increase sperm concentration and motility after busulfan-induced testicular damage in mice. Further research revealed that Opp and Ppp might promote spermatogonia proliferation, which improved blood-testis barrier (BTB) recovery between Sertoli cells. Taken together, these high-arginine peptides could be used as a medication or therapeutic component of a diet prescription to improve the fertility of some oligoasthenospermia patients.